Molecular evolution of the internal transcribed spacers in red oaks (Quercus sect. Lobatae). (December 2019) - Vázquez, M. Lucía
Highlights: Three types of Internal Transcribed Spacers (ITS) of lengths 505, 609, 601 bp, referred to as ITS-S (small), ITS-M (medium), and ITS-L (large) were identified in red oak species.. Of these three ribotypes, only ITS-M is functional and ITS-L and ITS-S are pseudogenes. Bayesian analysis strongly supports the monophyly of the pseudogene clades (100% posterior probability) but fails to support the putative functional clade (ITS-M). A pattern of ITS incomplete and complete concerted evolution was found for the red oak species examined; incomplete concerted evolution is likely the result of recent divergence, ancient hybridization, and lineage sorting. The results of this work suggest that ITS is not suitable for tracking the phylogenetic relationships of red oaks. Future understanding of the red oak phylogenetic relationships will require extensive taxon sampling and phylogenomic studies. Abstract: Previous studies of the Internal Transcribed Spacers of the nuclear ribosomal DNA (ITS) in sections Quercus (white oaks), Protobalanus (intermediate or golden cup oaks), Cerris (Cerris oaks), and Ilex (Ilex oaks) suggest that ITS regions undergo full concerted evolution in oaks; however, ITS evolution patterns in red oaks (section Lobatae ) are unknown due to scant representation in published work. To determine whether full concerted evolution occurs in red oaks, the purpose of this study was to examine ITS sequences from 40 red oak species. The results show incomplete concerted evolution and the presence of three ITS ribotypes of lengths 505, 609, 601 bp, hereafter referred to as ITS-S (small), I ITS-M (medium), and ITS-L (large), respectively. Thirty species had only one ribotype (ITS-M), nine species had two ribotypes (different combinations of ITS-L, ITS-M, and ITS-S), and only one species had all three ribotypes. Furthermore, examination of these three ribotypes showed that only ITS-M is putatively functional and ITS-L and ITS-S are pseudogenes. Bayesian analysis strongly supported (100%) two pseudogenes clades but provided weak support for the monophyly of a putative functional clade (ITS-M); moreover, within the "functional" clade, species relationships were uncertain and, in most cases, sequences from the same species failed to group together. The results of the current study suggest that ITS may not be appropriate for phylogeny reconstruction of red oaks due to low levels of interspecific variation and incomplete concerted evolution.